Witch of the wolves - Archer, Kaylee (St. Martin's Griffin, 2025)
"When a powerful witch discovers she's the daughter of an Alpha werewolf and is taken by his Pack, she's determined to break free all the while denying her attraction to her abductor. Witch of the Wolves is perfect for fans of A Court of Thorns and Roses and From Blood and Ash. Cordelia Levine comes from a long line of powerful witches. She's been flying under the radar in the human world, focused on strengthening her magic. She loves working at her aunt's apothecary in London, secretly serving supernaturals. Until the truth about her family is revealed. She always assumed her enhanced sense of smell came from her French perfumer father. But when Bishop Daniels abducts Cordelia at the request of her father, the Alpha, Cordelia learns she's a lycan--sharing both witch and werewolf traits. She's brought to Trevelyan, the pack estate, under the guise of protection from foreign threats who want to use her to continue their bloodline. She quickly learns that to keep her from being sold off to another pack, her father intends to give Cordelia as a mate to Bishop. His second in command and the future Alpha. Cordelia refuses to accept this as her fate. She can't rely on her magic alone to escape and when she learns Bishop plans to challenge her father's power, she reluctantly begins to trust him. The cracks within the Pack become evident and something is bound to break. And Cordelia and her growing desire for the man who shouldn't set her on fire are right at the center of it all. Witch of the Wolves is the first book in this Victorian romantasy series, featuring an intense and sexy romance and a world on the brink of change"-- Provided by publisher.